Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO307 - Jörg Geldmacher; Christian Timm; Mia Schumacher (PANGAEA, 2025)
Raw multibeam bathymetry data were collected aboard RV SONNE during cruise SO307 Madagaskar/Indico using a 12kHz Kongsberg EM 122 multibeam echosounder with 2x2 beam width. The expedition took place during 2024-09-12 – 2024-10-28 from Durban to Durban (South Africa) in the Indian Ocean. During the SONNE expedition SO307, scientific work was carried out for the geological main project (MADAGASCAR), a biological oceanography sub-project (INDICOM) and a biological sub-project (MADAGASCAR-BIO). The Madagascar Ridge (Southwest Indian Ocean) is ideal to explore the cause(s) of seafloor bathymetric anomalies, because it formed during the breakup of Gondwana, but the process behind its emplacement is controversial. Proposed origins include thinned continental crust, a hotspot-generated aseismic ridge or uplift due to buoyant, melt- depleted mantle. The overall aim of INDICOM is to investigate biological and biogeochemical processes that affect the turnover of organic matter in the deep Indian Ocean. The investigations of MADAGASCAR-Bio aim at: (1) Recording and describing the diversity of selected groups of the benthic communities of the Madagascar Ridge, (2) Uncovering cryptic species, (3) Testing the hypothesis about the function of oceanic ridges and their parallel running currents as corridors for the dispersal of benthic species, (4) Studying the availability of nutrients into the study area by sediment analyses ( extquotesingletotal carbon extquotesingle, TC and extquotesingletotal organic carbon extquotesingle, TOC). Data were recorded outside EEZs. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by GEOMAR Helmholtz Centre for Ocean Research, provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.